Validação de índice de conforto térmico e zoneamento bioclimático da bovinocultura de leite - Tonello, Cleiton Luiz (2011)
Aiming to develop a thermal comfort index for dairy cattle (TCIdc) there were used 150 Holstein dairy cows semi-confined in three locations (Cascavel - PR, Chapecó - SC and Erechim - RS). The environmental variables considered were: air temperature, air humidity, wind speed and black globe temperature that were used to calculate the TCIdc. The recorded responses of animals to the environment were: rectal temperature (RT), respiratory rate (RR) and level of daily milk production (MP). The interaction of these animals responses to the environment were described by means of path analysis and regression. To determine the bioclimatic zoning of dairy cattle in southern Brazil, with the thermal comfort index for dairy cattle (TCIdc) and milk production decline (DMP) of cows with high and low production at the temperatures in this region, were used daily average meteorological data from 69 weather stations distributed throughout the southern region of Brazil With the values of environmental variables, DMP and TCIdc were traced the contours of these variables to southern Brazil through the program ARCGIS. The index was developed using principal component analysis and compared with some indices of thermal comfort using correlation analysis. The rate estimated by the first principal component (Y1) has 56.76% of explanations of climate variables analyzed and obtained correlation of 0.2034 with the rectal temperature, respiratory rate of 0.1581 and -0.2535 with the level of milk production of cows, considered the best index to evaluate the thermal stress of Holstein cows in lactation. In animals of high milk production the air temperature and black globe temperature has more effect on the RR and RT, respectively, and high partial pressure of steam causes a reduction of milk production. For animals of the low production TCIdc correlated with RT (r = 0.1563) and RR (r = 0.1246) in animals of high production obtained with RT correlation of 0.2942 and 0.3646 for RR, proving to be the most efficient index to characterize the physiological changes of the animals to the environment of the locations analyzed. The most stressful parts of southern TCIdc showed values ranging from 38 to 42 with a decline in milk production for animals of low production (DMP<20) at 2 to 3 kg.vaca-1.day-1 and production decline for animals of high milk production (DMP>20) from 3 to 5 kg.vaca-1.day-1. In the state of Parana region of Campos Gerais, South Central and part of the region Central in the state of Santa Catarina throughout the central plateau, the northern part and valley catarinense and the state of Rio Grande do Sul the region Serra gaucha and top fields of the Serra gaucha region are considered more appropriate for dairy cow.